Survey on Technical in Smart farming - Patil, Rudragoud; Vishwanth Y, (IJRDO -Journal of Computer Science Engineering, 2021)
Smartphones are very effective tools for increasing their power and capacity, smartphones allow end users to perform several tasks and be always notify about their updates . API are made to efficient and useful data that is to be provided  to the farmers, for better understand the information of weather forecast in regional language. ”Traditional to Technical Farming ” provides tool for farmers with all the information about land, crops management, profit that they can make by growing a particular crop on their land, to increase productivity by proper use of Fertilizers. TTF, is one such application that can bridge  the gap and it helps to provide the farming community with better solutions for the proper management of their land, crop management, proper use of fertilizers , diseased plants in better manner by taking “SOIL TEST”